2022
DOI: 10.1039/d1gc03999g
|View full text |Cite
|
Sign up to set email alerts
|

An integrated process for the valorization of corn stover promoted by NaCl in a GVL/H2O system

Abstract: An integrated green process for the valorization of corn stover promoted by NaCl in GVL/H2O was developed. With the addition of NaCl in 25% GVL/H2O at 170 °C for 2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…GVL is also a biomass-derived green solvent that has similar properties as GBL. In the previous work, 31 GVL contents in GVL/H 2 O system showed a significant effect on the transformation of corn stover, and reached a maximum of 46.4% in 25% GVL/H 2 O. In terms of corn stover transformation, GBL/H 2 O outperformed the above three co-solvent systems.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…GVL is also a biomass-derived green solvent that has similar properties as GBL. In the previous work, 31 GVL contents in GVL/H 2 O system showed a significant effect on the transformation of corn stover, and reached a maximum of 46.4% in 25% GVL/H 2 O. In terms of corn stover transformation, GBL/H 2 O outperformed the above three co-solvent systems.…”
Section: Resultsmentioning
confidence: 67%
“…The change of GBL or GVL contents in solvent systems, on the other hand, increased the co-conversion and dissolution of hemicellulose and lignin. It was previously reported that 25% GVL /H 2 O gave notably higher hemicellulose (74.4%) and lignin (51.4%) removal, while 89.5% cellulose was kept intact at 160 °C for 2 h. 31 Compared to GVL, GBL exhibited better performance on the simultaneous removal of hemicellulose and lignin (Fig. 1(B)).…”
Section: Performance Of Gbl/h 2 O Co-solvent On the Transformation Of...mentioning
confidence: 76%
See 2 more Smart Citations
“…The process flexibility enhances the techno-economic viability and considers the demands at different levels of the value chain. 24,25 Related approaches have been proposed to valorize agro-industrial residues such as corn stover, 26 sugarcane, 27 marine, 25 and farming 28 waste. The valorization strategy considers two alternatives: GVL solvolysis in the first conversion stage, followed by the thermal valorization of solids via fast pyrolysis at 500 °C to produce different liquid fractions rich in sugars, phenols, and furanics.…”
Section: Introductionmentioning
confidence: 99%